Promoting opioids, a story about how to influence medical science and opinions - Bernisson, Maud; Sismondo, Sergio (Frontiers in Medicine, 2024)
Key origins of the opioid crisis in the US lie in some pharmaceutical companies’ substantial efforts to sell prescription painkillers. To legitimize opioids, the companies built up a body of medical science and opinions, and channels with which to communicate. Archival searches found 876 contracts that together provide information on how Mallinckrodt, an opioid manufacturer, attempted the ghost-management of medicine. These records—available because of litigation–involved contract research organizations, medical education and communication companies, publishers, professional societies, researchers, and other people who could be Mallinckrodt’s agents. Together, they produced and circulated scientific messages to increase physicians’ comfort with prescribing opioids. This article gives an overview of that activity, as seen in the contracts and related documents.